Fabrication and characterization of ciprofloxacin loaded niosomes for transtympanic delivery - Mhlanga, Asavela (Rhodes University, Faculty of Pharmacy, Pharmacy)
Ciprofloxacin (CPH) is a broad-spectrum antibiotic used to treat bone, joint, and skin infections. It is commercially available as an extended-release tablet and as a cream dosage form. CPH is a bactericidal active pharmaceutical ingredient (API) of the fluoroquinolone drug class. It inhibits deoxyribonucleic acid (DNA) replication by inhibiting bacterial DNA topoisomerase and DNA gyrase enzymes. Common adverse effects include nausea, vomiting, unusual fatigue, pale skin, and may increase the risk of tendinitis, which could be a major concern. CPH is, according to the Biopharmaceutics Classification System (BCS), classified as a BCS class IV drug exhibiting low oral bioavailability, low solubility, and intestinal permeability. CPH was chosen as a good candidate for the study because of its stability in solutions, its low molecular weight (331.4 g/mol), and its moderate lipophilicity (log P = 0.28) [16]. The use of conventional ear drops in the ear is effective, avoids hepatic first metabolism and extensive protein binding and may reduce adverse effects as a low dose may be used to achieve a therapeutic effect. However, conventional ear drops and oral antibiotics have a long onset of action and have to be taken/applied in short intervals. For convenience and assurance of a long residence time in the ear, CPH may be delivered by using a niosomal formulation, a liquid at room temperature, to allow administration into the ear without the need to constantly apply the ear drops for long periods of time. A simple, rapid, precise, accurate, reproducible, and specific reversed-phase high-performance liquid chromatography (RP-HPLC) method using ultraviolet (UV) detection for the quantitation of CPH was developed and optimized using a central composite design (CCD). The method was validated using International Conference on Harmonisation (ICH) guidelines and was found to be linear, precise, accurate, and specific for the analysis of CPH. Since the method is specific, it was used to quantify CPH in commercial and experimental formulations and monitor CPH released during in-vitro release testing. The compatibility of CPH and potential excipients was investigated during preformulation studies using Fourier transform infrared spectroscopy (FT-IR) and differential scanning calorimetry (DSC) to identify and select suitable excipients for use during formulation development activities. No apparent interactions were evident between CPH, and the excipients tested. The probe sonication method was used to manufacture CPH loaded niosomes using different surfactants/surfactant combinations, and a combination of Tween® 80: sodium lauryl sulfate (SLS) was found to be the best composition in terms of both entrapment efficiency and Zeta potential. The limits for the independent input variables used for the manufacture included amplitude, sonication time, and amount of cholesterol were determined. Design of experiments (DOE) was used to design the study. The input variables investigated included amplitude, amount of cholesterol, and sonication time. The output or responses monitored included Zeta potential, vesicle size, polydispersity index (PDI), and entrapment efficiency. Non-ionic surfactant systems are predominantly stabilized by steric stabilization, and there is only a minor electrostatic element from adsorbed hydroxyl ions. With the inclusion of SLS it is to be expected that Zeta potential will be a contributing factor. DOE using Box-Behnken design (BBD) and response surface methodology (RSM) in addition to Artificial Neural Networks (ANN) were used for the optimization of the formulation. The optimized formulation had a composition of 1 g cholesterol, 1 g of Tween® 80, 1 g of SLS and was prepared at an amplitude of 11.294 % with a sonication time of 3.304 minutes. The formulation exhibited zero-order release kinetics and had an average pH of 7.45. The formulation was stored at 4 ℃ and 25 ℃ and was assessed for vesicle size, entrapment efficiency, Zeta potential, colour, lamellarity, and PDI every 7 days for 4 weeks. The lead formulation stored at 4 ℃ was more stable than the formulation at 25 ℃ in terms of entrapment efficiency, PDI and vesicle size during the 4-week period. CPH loaded niosomes for transtympanic delivery in the treatment of otitis media were developed and optimized. The technology exhibits sustained release of CPH and has the potential for further development and optimization.
Keywords: Drug delivery systems; Liposomes; Ciprofloxacin; Quinolone antibacterial agents; Drug carriers (Pharmacy); Drug stability; Lamellarity; Niosomes